Pyrocarbon proximal interphalangeal joint arthroplasty - Mcguire, Duncan Thomas (Department of Health and Rehabilitation Sciences, 2015)
Arthritis of the proximal interphalangeal joint of the hand can be debilitating disease resulting in pain and stiffness. Treatment is initially conservative but with diseasse progression surgical treatment often becomes necessary. Arthroplasty is one of the surgical options available.